Data Compression and Transform Coding for Improved Performance in Optical-Fiber Communication - Abdulmanam S. Abdulwhab; Zeyad Moh. Elkwash; Jamal Abd Eltayef Esghaer; Ahmed Alhadi Ahmed (Surman Journal of Science and Technology, 2025)
The ever-growing volumes of data demand efficient storage and reliable communication solutions. Compressing information without compromising quality is a crucial challenge faced by modern systems. Meanwhile, the need for high-speed, long-distance data transfer continues to push the boundaries of optical transmission technologies. Overcoming these dual obstacles is essential for enabling innovative applications across diverse sectors. in this research, Huffman and LZW algorithms were used and achieved good results. An average compression ratio of 1:47 was obtained for text files, while an average compression ratio of 1:10 was achieved for audio files. Huffman coding, which is a lossless data compression method, provided a higher throughput rate, making it suitable for applications where processing speed is a priority. On the other hand, the LZW algorithm, which is also a lossless technique, provided a higher compression ratio without adding additional encoding to the files, although this came at the cost of higher (RAM) Random Access Memory consumption. In the field of audio compression, a down sampling algorithm was used along with the Fast Fourier Transform (FFT) to effectively reduce the sampling rate of audio files. This approach resulted in good compression ratios while preserving the sound characteristics, as evidenced by the obtained Signal-to-Noise Ratio (SNR), Mean Square Error (MSE), and Peak Signal-to-Noise Ratio (PSNR) values. By fine-tuning the down sampling factor, which was found to give good results and provide, an excellent balance between compression efficiency and sound quality when its value was between 3 and 10. The bidirectional fiber optic link also demonstrated good performance in data transmission, with low loss values, excellent Bit Error Rate (BER) value less than 1 and Q-factor higher than 7, high Optical Signal-to-Noise Ratio (OSNR) levels above 18dB, This optical communication system can find applications in high-speed data transmission, long-distance communications, and other areas that require reliable and high-bandwidth data transfer. Overall, this research highlights the multi-faceted capabilities in both data compression and optical communications. By the seamless integration of Huffman and LZW algorithms, audio down sampling, and fiber optic technologies, a system was implemented and simulated to provide a solution that can meet a wide range of applications, from efficient data storage and transmission to high performance communication systems.